The impact of cohort substance use upon likelihood of transitioning through stages of alcohol and cannabis use and use disorder: Findings from the Australian National Survey on Mental Health and Wellbeing. (5th March 2018) - Degenhardt, Louisa; Glantz, Meyer; Bharat, Chrianna; Peacock, Amy; Lago, Luise; Sampson, Nancy; Kessler, Ronald C.
Abstract: Introduction and Aims: We used population‐level Australian data to estimate prevalence, age of onset and speed of transitions across stages of alcohol and cannabis use, abuse and dependence, and remission from disorder, and consider the potential impacts that an individual's age cohort's level of substance use predicted transitions into and out of substance use. Design and Methods: Data on use, DSM‐IV use disorders, and remission from these disorders were collected from participants ( n = 8463) in the 2007 Australian National Survey of Mental Health and Wellbeing using the Composite International Diagnostic Interview. Results: Lifetime prevalence (95% confidence interval) of alcohol use, regular use, abuse and dependence were 94.1% (93.3–94.8%), 64.5% (62.9–66.2%), 18.7% (17.4–19.9%) and 4.0% (3.4–4.6%). Lifetime prevalence of cannabis use, abuse and dependence were 19.8% (18.6–20.9%), 4.4% (3.8–5.0%) and 1.9% (1.5–2.4%). Among those with the disorder, rates of remission from cannabis abuse, alcohol abuse, cannabis dependence and alcohol dependence were 90.5% (87.4–93.6%), 86.2% (83.8–88.7%), 79.6% (71.1–88.1%) and 53.8% (46.6–61.0%). Increases in the estimated proportion of people in the respondent's age cohort who used alcohol/cannabis as of a given age were significantly associated with most transitions from use through to remission beginning at the same age. Discussion and Conclusions: Clear associations were documented between cohort‐level prevalence of substance use and personal risk of subsequent transitions of individuals in the cohort from use to greater substance involvement. This relationship remained significant over and above associations involving the individual's age of initiation. These findings have important implications for our understanding of the causal pathways into and out of problematic substance use.